The Fault in Our Astrocytes - cause or casualties of proteinopathies of ALS/FTD and other neurodegenerative diseases? - Bustos, Lynette M.; Sattler, Rita (Frontiers in Molecular Medicine, 2023)
Many neurodegenerative diseases fall under the class of diseases known as proteinopathies, whereby the structure and localization of specific proteins become abnormal. These aberrant proteins often aggregate within cells which disrupts vital homeostatic and physiological cellular functions, ultimately contributing to cell death. Although neurodegenerative disease research is typically neurocentric, there is evidence supporting the role of non-neuronal cells in the pathogenesis of these diseases. Specifically, the role of astrocytes in neurodegenerative diseases has been an ever-growing area of research. Astrocytes are one of the most abundant cell types in the central nervous system (CNS) and provide an array of essential homeostatic functions that are disrupted in neurodegenerative diseases. Astrocytes can exhibit a reactive phenotype that is characterized by molecular changes, as well as changes in morphology and function. In neurodegenerative diseases, there is potential for reactive astrocytes to assume a loss-of-function phenotype in homeostatic operations such as synapse maintenance, neuronal metabolic support, and facilitating cell-cell communication between glia and neurons. They are also able to concurrently exhibit gain-of-function phenotypes that can be destructive to neural networks and the astrocytes themselves. Additionally, astrocytes have been shown to internalize disease related proteins and reflect similar or exacerbated pathology that has been observed in neurons. Here, we review several major neurodegenerative disease-specific proteinopathies and what is known about their presence in astrocytes and the potential consequences regarding cell and non-cell autonomous neurodegeneration.